What Future for Africas Manufacturing Sector in the New World Environment? Rethinking the Industrial Development Agenda in Sub-Saharan Africa (Global Journal of Human-Social Science, 2015)
Since independence, Africa is not mistress of her destiny, particularly in terms of industrialization strategy. Development paradigms followed over the last fifty years by African states are not developmentalist. They revealed their limit in the socio-economic transformation. Today, more than ever before, Africa needs a development agenda driven from the bottom up. The objective of this article is to revive the debate on alternative policies of industrialization in Africa: an endogenous industrialization policy, inclusive and progressive. While there may be a specifically African way in development, it is clear that the small cottage industry could be a pivot of development. The new industrialization policy must do from informal sector a nursery or incubator of industrialization and therefore a catalyst for structural transformation of the continent.
Keywords: endogenous development; industrialization strategies; informal sector; Africa